2012
DOI: 10.1111/j.1365-2966.2011.20287.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas sloshing, cold fronts, Kelvin-Helmholtz instabilities and the merger history of the cluster of galaxies Abell 496

Abstract: We investigate the origin and nature of the multiple sloshing cold fronts in the core of Abell 496 by direct comparison between observations and dedicated hydrodynamical simulations. Our simulations model a minor merger with a 4 × 10 13 M subcluster crossing A496 from the south-west to the north-north-east, passing the cluster core in the south-east at a pericentre distance of 100 to a few × 100 kpc about 0.6-0.8 Gyr ago. The gas sloshing triggered by the merger can reproduce almost all observed features, e.g.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 39 publications
10
80
0
1
Order By: Relevance
“…Bîrzan et al 2012) and the depths (Fe(r max )/Fe drop ) or the radial extent (r max /r 500 ) of the drops in our sample. Similarly, while the extended drop seen in NGC 5044 might be partly explained by its peculiar metal distribution in the sloshed gas (O'Sullivan et al 2014), sloshing process can probably not explain the (narrower) drops seen in other objects (Roediger et al 2011(Roediger et al , 2012.…”
Section: Central Metallicity Dropmentioning
confidence: 99%
“…Bîrzan et al 2012) and the depths (Fe(r max )/Fe drop ) or the radial extent (r max /r 500 ) of the drops in our sample. Similarly, while the extended drop seen in NGC 5044 might be partly explained by its peculiar metal distribution in the sloshed gas (O'Sullivan et al 2014), sloshing process can probably not explain the (narrower) drops seen in other objects (Roediger et al 2011(Roediger et al , 2012.…”
Section: Central Metallicity Dropmentioning
confidence: 99%
“…The ICM is rarely in perfect hydrostatic equilibrium because large-scale accretion of matter, turbulent motions, gas sloshing, AGN, and galaxy motions are considerably and regularly perturbing the gas (e.g., Schuecker et al 2004, Henry et al 2004Vogt & Enßlin 2005;Enßlin & Vogt 2006;Sanders et al 2010;Roediger et al 2012). …”
Section: Metallicity In Cluster Outskirtsmentioning
confidence: 99%
“…Markevitch & Vikhlinin 2007). Roediger et al (2012a) found that the boxy structure in A496 arises due to the development of Kelvin-Helmholtz instabilities along cold fronts. The cold front appears strongest around the N edge of the SW group core where the outer hot atmospheres of each group are colliding.…”
Section: Spatially Resolved Spectroscopymentioning
confidence: 99%